Environmentally sustainable policies and practices in hospitality - Costa, António Maria Pinto de Andrade Milheiro da (2022)
Tourism has become increasingly prominent, as one of the fundamental pillars for the development of the European economy and for social wellbeing, having registered enormous growth in recent decades. But, alongside economic and social prosperity, this growth has also brought about a significant increase in the carbon footprint of this sector. In fact, the uncontrolled and unsupervised growth of the hotel industry, among other aspects of the tourism sector, had and continues to have direct negative consequences for the environment and indirect consequences for the wellbeing and health of local populations. Having had a large carbon footprint for many years, tourism is today one of the economic sectors that is under greater pressure to reverse this process and achieve carbon neutrality. Although measures have already been taken in this direction, there are still many challenges to overcome, particularly at the local level, so that tourism may effectively fulfill its potential for economic prosperity and social welfare. The study and research work conducted within this dissertation, aimed at assessing the state of implementation of environmentally sustainable measures in the hospitality industry, whilst shedding some light on the motivations for managers of Portuguese hotels to improve their sustainable policy and on the factors that could positively and negatively impact their decisions. We wanted to assess whether factors such as regional economy, culture and legislation would affect the decisionmaking of hotel managers concerning Environmentally Sustainable Policies and Practices (ESPP) and what would be the revenues for the stakeholders. Even though many studies have been recently conducted on the need and state of implementation of ESPP in hospitality, very few have investigated aspects related with legislation or with the beliefs, motivations and awareness of hotel managers in Portugal. Most of the so far conducted studies have been of objective nature, assessing levels and breadth of implementation of ESPP in the tourism sector. In our work, we have combined an objective with a subjective assessment, supported on a review of the emergent literature and backed by an empirical work of collecting and analysing data from relevant stakeholders. We have therefore adopted a mixed methodology approach, where we have used closed-end questionnaires towards two audience segments (hotel managers and hotel guests) and semi-structured one-toone interviews with hospitality professionals (hotel managers). A statistical analysis was conducted on the quantitative data collected with the questionnaires to derive descriptive statistics useful for assessing the formulated hypothesis. A grounded theory approach was implemented using the qualitative data gathered in the one-to-one interviews, leading to the acquisition of a better understanding of the reality on the field. The developed analysis was performed using both a deductive coding technique, based on concepts that were present in the previously formulated research questions, and an inductive coding technique whereby new concepts were identified during the data analysis. Such combination enabled to sustain some of the initial concepts and formulate new ones which overall contributed to the assessment and extension of the formulated themes. Our results corroborate to a large extent the formulated theories and highlight that there is significant awareness from the involved stakeholders on the most well known aspects and factors of ESPP and their consequent impacts, as well as a great inclination to be involved. However, there is not a consistent understanding of the existence and beneficial impact of many other possible measures. Furthermore, when it comes to relevant standards and legislation, the lack of consolidated awareness and experience is more pronounced as it is concerning the breadth of environmentally friendly measures that can be adopted and the varying benefits that can be derived from their implementation. Likewise, cooperation between major stakeholders, namely governmental entities, regional and national authorities, tourism associations, and hospitality units is still insufficient to enable effective and sustained engagement of all parties. Although there is non-negligible enlightenment of the general public concerning the importance of ESPP it remains less clear how such perception influences choices and effective collaboration during hotel stays. Overall, our study suggests that hotels should embrace a more holistic approach to the definition and implementation of ESPP, clearly embedding them into the hotel’s modus operandi and stimulating relationships and cooperation with interested stakeholders, including the guests.